An exploration of online behaviors and social media use among hookah and electronic-cigarette users - Alissa R. Link; Philip B. Cawkwell; Donna R. Shelley; Scott E. Sherman (Addictive Behaviors Reports, 2015)
Introduction: The purpose of this study was to explore the relationship between social norms and attitudes towards ENDS and hookah and use of these products. Methods: We conducted surveys with hookah and ENDS users who regularly used the Internet and social media and analyzed the primary social media account (e.g. Facebook) of each participant, coding all references to nicotine or tobacco products. The survey included domains on perceived favorability, perceived vulnerability and subjective norms. Results: We surveyed 21 ENDS users and 20 hookah users. Both groups used the Internet to look up information about their respective tobacco product (95% for hookah vs. 90% for ENDS). Seventy percent of hookah users had references to hookah on their social media profiles while 43% of ENDS users had references to ENDS on their page. The majority of both groups were exposed to content posted by friends in their social media network about their respective products online. Those who posted on social media about hookah and those who read about ENDS online had lower perceived vulnerability to the health risks associated with tobacco products. Conclusions: Hookah and ENDS users actively use the Internet and social media to obtain and share information about nicotine/tobacco products. Study participants who use hookah were more likely to share photos and discuss hookah related activities via social media than those who use ENDS. Social networks also represent valuable and untapped potential resources for communicating with this group about risks and harm reduction related to emerging nicotine/tobacco products.